Taking Stock in Wildlife Crime Research: Trends and Implications for Future Research. Issue 1 (2nd January 2020) - McFann, Sara C.; Pires, Stephen F.
ABSTRACT: Wildlife crime is an emerging topic of study within criminology and criminal justice (CCJ). This study provides the first-ever systematic review of the state of wildlife crime research by CCJ scholars to describe and better understand how it has evolved over time and where the opportunity for expansion exists. Data gathered from a search of the Criminal Justice Abstracts database is analyzed to address ten hypotheses concerning overall trends. Findings show that quantitative studies are rare in the literature with the majority of studies being conceptual or theoretical in nature. Further, the literature is concentrated among researchers, countries, universities, and journals, and that research relies heavily on certain methods, foci, and theories.